The Reciprocal Relationship Between Cell Adhesion Molecules and Reactive Oxygen Species - Muayad Al-Hadi; Alexander G. Nikonenko; Vladimir Sytnyk (Cells)
Cell adhesion molecules (CAMs) are cell-surface-localized proteins mediating interactions of cells with other cells and the extracellular matrix. CAMs influence cell behavior and survival by inducing various intracellular signaling cascades that regulate diverse cellular processes including cytoskeleton remodeling and gene expression. Here, we review the evidence demonstrating that the levels, subcellular distribution, and binding affinities of CAMs of several major families including integrins, cadherins, immunoglobulin superfamily, and selectins are regulated by intracellularly generated or extracellular reactive oxygen species (ROS). Remarkably, CAMs themselves induce ROS production in response to binding to their ligands by activating lipoxygenases or NADPH oxidases or influencing ROS generation in mitochondria. CAM-dependent ROS production is essential for CAM-mediated cell adhesion and CAM-dependent intracellular signaling. Importantly, CAMs also protect cells from the ROS-induced cell death by stimulating the synthesis of antioxidants and suppressing the cell death signaling. A better understanding of the role ROS play in controlling CAM functions and mechanisms of this control may pave the way to modulating the functions of CAMs in various disorders associated with abnormal cell adhesion.